2020
DOI: 10.1186/s12879-020-4852-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of extrapulmonary tuberculosis using the MPT64 antigen detection test in a high-income low tuberculosis prevalence setting

Abstract: Background: Extrapulmonary tuberculosis (EPTB) poses diagnostic challenges due to the paucibacillary nature of the disease. The immunochemistry-based MPT64 antigen detection test (MPT64 test) has shown promising results for diagnosing EPTB in previous studies performed in low-resource settings, with higher sensitivity than microscopy and culture. The aim of this study was to investigate the performance of the MPT64 test in a routine clinical setting in a high-income low TB prevalence country. Methods: Extrapul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…The present study was performed on frozen specimens that had been collected as part of a larger prospective study conducted at Haukeland University Hospital, Bergen, Norway, between January 2015 and June 2016 27 . The study includes 47 specimens that were also included in the larger study, and 39 additional specimens that did not meet the inclusion criteria in the larger study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study was performed on frozen specimens that had been collected as part of a larger prospective study conducted at Haukeland University Hospital, Bergen, Norway, between January 2015 and June 2016 27 . The study includes 47 specimens that were also included in the larger study, and 39 additional specimens that did not meet the inclusion criteria in the larger study.…”
Section: Methodsmentioning
confidence: 99%
“…The aims of the present study were to (1) evaluate the diagnostic accuracy of Ultra for diagnosing EPTB compared to routinely used culture and PCR tests in a clinical setting in the high-income low TB prevalence country Norway 26 , and (2) investigate the potential of Ultra as an add-on test to the existing routine tests to improve the rapid diagnosis of EPTB. a larger prospective study conducted at Haukeland University Hospital, Bergen, Norway, between January 2015 and June 2016 27 . The study includes 47 specimens that were also included in the larger study, and 39 additional specimens that did not meet the inclusion criteria in the larger study.…”
mentioning
confidence: 99%
“…The antigen-85 enzyme is also cable of binding with fibronectin that is an extra-cellular milieu of glycoprotein involved in several biological processes including immune responses. This contact seems to decrease phagocytosis of M. tuberculosis, supporting infection [35].…”
Section: Ag85bmentioning
confidence: 74%
“…Many studies showed that MPT64 exhibits good diagnostic efficiency for MTB. 20 , 21 Phosphate ABC transporter substrate-binding lipoprotein (PstS1) is a member of ABC transporters family and can be found intracellularly and extracellular. Alcaide et al developed a Multiplex Real-Time PCR assay for the quantitative detection of whiB3 and PstS1 and the results revealed high sensitivity and specificity especially for diagnosis of smear negative pulmonary TB.…”
Section: Introductionmentioning
confidence: 99%